1965
DOI: 10.1136/bmj.2.5460.509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment of Thyrotoxicosis on Exophthalmos

Abstract: MEDICIsOURNAL 509 28 days of onset of symptoms, were reported. Residual paralysis was found in only four cases of paralytic poliomyelitis occurring between 5 and 28 days after vaccination, an incidence of 1 in four and a half million doses administered. We are indebted to the many medical officers of health, hospital clinicians, general practitioners, and virologists who have co-operated in providing information concerning their patients, and to the Ministry of Health for the statistics on the use of oral vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1970
1970
1986
1986

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…G reig el al. expressed the same point of view [14] and quoted the confirmatory reports of W erner [39] patients indicated that in one-half of them exophthalmos increased after treatment with 131I. These reports of progression of exophthalmos following treatment of thyrotoxicosis refer almost always to limited increases of 2 mm or more in the proptosis rather than to the development of malignant exophthalmos which results in decreased vision, necessitates orbital decom pression, or results in loss of the eyes.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…G reig el al. expressed the same point of view [14] and quoted the confirmatory reports of W erner [39] patients indicated that in one-half of them exophthalmos increased after treatment with 131I. These reports of progression of exophthalmos following treatment of thyrotoxicosis refer almost always to limited increases of 2 mm or more in the proptosis rather than to the development of malignant exophthalmos which results in decreased vision, necessitates orbital decom pression, or results in loss of the eyes.…”
Section: Resultsmentioning
confidence: 53%
“…Though it is established that TSH is decreased rather than increased in untreated thyrotoxic exophthalmos [30] and hence cannot be the cause of the exophthalmos, the minimal increases in proptosis described by D obyns and H aines [10] and others [14,15,17] which follow upon treatment of the hyperthyroidism could result from actual or impending hypothyroidism. Also, the fact that malignant exophthalmos can occur in spontaneous thyroid hypofunction in which TSH is increased [30] raises the possibility that in certain individuals malignant exophthalmos could have resulted from TSH excesses.…”
Section: Resultsmentioning
confidence: 99%
“…Dabei hat die Geschwindigkeit, mit der ein euthyreotes Stadium erreicht wird, keinen Einflul~ auf den Verlauf der e. 0. [13]. Exakte Vergleiche sind wegen unterschiedlicher Beurteilungskriterien der einzelnen Beobachter schwer mSglich.…”
Section: Diskussionunclassified
“…In turn, the net damage within the thyroid from a given radiation dose in rad depends on distribution and on cell and tissue radiosensitivity (Greig, 1965).…”
Section: Distribution Of 1311 Throughout the Tissue And Cellsmentioning
confidence: 99%
“…10, OCTOBER 2.8 per cent (Nofal, Beierwaltes, and Patno, 1966). Radio-isotopes are presumed to act by interference with the replicative mechanism of the thyroid follicular cell (Greig, 1965), and the implication is that the eventual end-point of radio-iodine therapy is hypothyroidism in all patients.…”
mentioning
confidence: 99%